FAKTOR-FAKTOR PENENTU KEPUTUSAN PEMBELIAN PRODUK AIR MINUM MEREK AQUA KEMASAN GALON (STUDI KASUS DI WILAYAH MENUR PUMPUNGAN SUKOLILO SURABAYA ) - firdaus firdaus; Adhi Tri Tunggal (Universitas Dr. Soetomo, 2022)
This research is a quantitative research with the determination of the sample using purposive sampling technique. In this study, data collection was carried out by means of interviews and questionnaires. Informants in this study were people who had purchased aqua bottled drinking water products in the Menur Pumpungan Sukolilo area of Surabaya. The setting of this research was carried out in the Menur Pumpungan Sukolilo area of Surabaya. The theory used in data analysis in this study uses the theory of Kotler. The results of the data findings indicate that from the overall analysis of the factors that are suspected of causing purchasing decisions for gallon packaged aqua products, there are 6 factors including the affordable price of aqua gallons offered, the factor of aqua gallon products according to age, the factor of buying aqua products because the community is in the same class, advertising factors through business cards and factors according to self-confidence. Among these factors, the price of aqua gallons offered at affordable prices is the dominant factor that is highly considered in purchasing decisions for gallon aqua products in the Menur Pumpungan Sukolilo area of Surabaya. These results are evidenced by the eigent value of 7.172 which is the largest value of the other factors